Two theorems about C2 and some more. (17th April 2016) - Tchougréeff, A. L.; Dronskowski, R.
ABSTRACT: The story of C2 continues to fascinate chemists spinning around a possibility of quadruple bonds for p -elements and discussing a wealth of options for the nature of an unconventional fourth bond. This led to lively discussions about the ways of counting or measuring bonds, and the interplay between the bond strength (energy), its length, and rigidity/stiffness (elasticity). Even old concerns about the possibility of theorems in chemistry and thus of the place of chemistry among 'true' sciences had been revived. We show that under some mild conditions certain exact statements (lemmas and theorems) about the C2 molecule can be relatively easily proven which, if not resolves the controversy entirely, at least provides some theoretical reference points to the discussion. Some more general consequences from this experience are discussed as well. GRAPHICAL ABSTRACT: